High electric field-induced strain with ultra-low hysteresis and giant electrostrictive coefficient in barium strontium titanate lead-free ferroelectrics. Issue 2 (February 2019) - Jin, Li; Luo, Wenting; Hou, Lei; Tian, Ye; Hu, Qingyuan; Wang, Liang; Zhang, Lin; Lu, Xu; Du, Hongliang; Wei, Xiaoyong; Yan, Yan; Liu, Gang
Abstract: Ferroelectrics with high electrostrictive properties are of great interest in fundamental researches and industrial applications. In this work, the phase structural evolution, dielectric properties as well as electrostrictive properties in barium strontium titanate [(Ba1- x Sr x )TiO3, BST] lead-free ferroelectrics with x from 0.05 to 0.4 were investigated in details. High electric field-induced strain (∼0.2%) at 60 kV/cm are obtained in x = 0.05 and 0.1 compositions. More importantly, almost purely positive strains with ultra-low hysteresis (<8%) determined from bipolar strain-electric field curves are observed in compositions with x from 0.05 to 0.3, suggesting the dominating role of electrostrictive effect. Temperature-insensitive and composition-insensitive longitudinal electrostrictive coefficient Q 33 for BST ceramics with giant values from 0.0409 m 4 /C 2 to 0.0479 m 4 /C 2 is identified. These features suggest that BST ceramics not only possess high electric field-induced strain with ultra-low hysteresis and giant Q 33, but also are good candidates for potential application in high-precision actuator devices.